Local Cryogenics for the SIS100 at FAIR. Issue 1 (November 2015) - Eisel, T; Chorowski, M; Iluk, A; Kauschke, M; Kollmus, H; Malcher, K; Polinski, J; Streicher, B
Abstract: In the coming years a new international accelerator Facility for Antiproton and Ion Research (FAIR), one of the largest research projects worldwide, will be build close to Darmstadt in Germany. FAIR will provide antiproton and ion beams with unprecedented intensity and quality. One of its major accelerators will be a synchrotron called SIS100 having a circumference of about 1100 meters. The SIS100 tunnel will house a complex cryogenic system supplying up to 20 kW cooling capacity @ 4.5 K to about 300 superconducting fast ramped magnets and other physics equipment. The planned SIS100 local cryogenic system can be principally divided into three sections each fed from a separate Feed Box. Every Feed Box supplies 4.5 K helium for magnet, vacuum chamber, cryo collimator, current lead and bus-bar cooling as well as 50 K helium for the current lead and thermal shield cooling, independently to two sixth of the ring. Each sixth of the ring, so called sextant, consists of a cold arc and a straight warm section. By-pass Lines circumvent the straight warm sections of the sextants, where warm equipment (e.g. normal conducting cavities and magnets) is located. Between the warm equipment, are superconducting magnets located which also need to be supplied from the By-pass Lines with helium and cold electrical connections. The By-pass Lines are Polish in-kind contribution, coordinated by the Jagiellonian University of Krakow and will be designed, manufactured and commissioned by the Wroclaw University of Technology. In this paper the SIS100 local cryogenic system will be described with focus on the By-pass Lines and on magnet cooling including the balancing of differences between dipole and quadrupole circuits and the coping with dynamic loads.